2019
DOI: 10.2134/jeq2018.11.0418
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Edge‐of‐Field Phosphorus Losses in Ontario, Canada: Importance of the Nongrowing Season in Cold Regions

Abstract: Agricultural P losses are a global economic and water quality concern. Much of the current understanding of P dynamics in agricultural systems has been obtained from rainfall-driven runoff, and less is known about cold-season processes. An improved understanding of the magnitude, form, and transport flow paths of P losses from agricultural croplands year round, and the climatic drivers of these processes, is needed to prioritize and evaluate appropriate best management practices (BMPs) to protect soil-water qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 55 publications
4
68
2
Order By: Relevance
“…1) in Ontario, with subsequent determination of SRP at both laboratories. At the Ontario sites, samples were collected at 2‐ to 8‐h intervals throughout storm events to capture the entire event hydrograph, including baseflow at the beginning and end of the event as described in Plach et al (2019). At the Ohio sites, water samples were collected at 6‐h intervals, and the four samples collected in a 24‐h period were composited into a single sample for that 24‐h period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) in Ontario, with subsequent determination of SRP at both laboratories. At the Ontario sites, samples were collected at 2‐ to 8‐h intervals throughout storm events to capture the entire event hydrograph, including baseflow at the beginning and end of the event as described in Plach et al (2019). At the Ohio sites, water samples were collected at 6‐h intervals, and the four samples collected in a 24‐h period were composited into a single sample for that 24‐h period.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the evidence of enhanced P loss in tile drains has emerged from studies in fine-textured soils, where connectivity between surface soils and tile drains is increased by the presence of macropores (Stamm et al, 1998;Beauchemin et al, 1998). Research targeting clay-rich agricultural sites in Ohio, Indiana, and Ontario in North America has shown substantial P loss via tile drainage, with similar concentrations in surface and subsurface discharge King et al, 2018;Plach et al, 2019). In contrast, studies in coarser-textured soils in Sweden (Andersson et al, 2013) and across Quebec (Beauchemin et al, 1998) and Ontario (Plach et al, 2018a(Plach et al, , 2019Lam et al, 2016) in Canada have shown smaller P concentrations in tile drainage relative to surface runoff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microclimate greatly influences snow characteristics in an area, so the is a need for differing planning to cope with too high rainfall (Plach et al, 2019). Meltsnow is the most influential source of irrigation in the area before the rainy season (Biemans., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Snowmelt and runoff over frozen or partially frozen soils are important, if not primary, processes for P transport in the northern watersheds, from the Chesapeake Bay to Lake Winnipeg. Indeed, runoff and P mobilization in the Lake Erie and Lake Winnipeg watersheds primarily occur throughout the nongrowing season (Macrae et al, 2007; Ford et al, 2018; King et al, 2018; Plach et al, 2019) and is most often dominated by spring snowmelt (Macrae et al, 2007), although large‐magnitude events can occur at other times of year, including the summer months (Macrae et al, 2010; Van Esbroeck et al, 2017). Mitigation strategies that are effective under rainfall‐dominated conditions during the growing season have not been successful during the winter period (Baulch et al, 2019; Kieta et al, 2018).…”
Section: Watershed Phosphorus Concerns Across Latitudesmentioning
confidence: 99%